BUDAYA SEKOLAH DALAM MEWUJUDKAN KARAKTER RELIGIUS - Septiyana Solekhah, Annisa; Muhroji (JS (JURNAL SEKOLAH), 2025)
Abstract: The objectives of the study are: (1) To describe the implementation of school culture in realizing the religious character of grade 4 students at SD Aisyiyah Unggulan Gemolong; (2) To describe the obstacles in implementing school culture in realizing the religious character of grade 4 students at SD Aisyiyah Unggulan Gemolong. The study is a descriptive qualitative study. The study was conducted at SD Aisyiyah Unggulan Gemolong. The subjects of the study included: the principal, vice principal for student affairs, grade 4 teachers and grade 4 students. The object of the study was school culture in realizing religious character. Testing the validity of the data with source triangulation and technique triangulation. Data analysis with interactive techniques. The results of the study indicate that: (1) The implementation of school culture in realizing religious character, includes: habituation through routine activities (by reading the Qur'an, memorizing the class entrance password, muroja'ah and congregational prayer (dhuha prayer and dhuhur prayer)), strengthening children's character in morals (by praying, 5S (senyum, salam, sapa, sopan and santun) and manners of eating), strengthening children's character through role models from teachers in behaving and providing motivation and evaluation of activities; (2) Obstacles to the implementation of school culture in realizing religious character, include: different student characteristics, teachers have not played their role as role models and children receive less attention from their parents. The study is expected to provide new information regarding school culture in realizing religious character in elementary schools, so as to foster good personalities in students. Keyword: character; religious character; school culture Abstrak: Tujuan penelitian yaitu: (1) Mendeskripsikan penerapan budaya sekolah dalam mewujudkan karakter religius siswa kelas 4 di SD Aisyiyah Unggulan Gemolong; (2) Mendeskripsikan kendala penerapan budaya sekolah dalam mewujudkan karakter religius siswa kelas 4 di SD Aisyiyah Unggulan Gemolong. Penelitian termasuk penelitian kualitatif deskriptif. Penelitian dilakukan di SD Aisyiyah Unggulan Gemolong. Subjek penelitian meliputi: kepala sekolah, waka kesiswaan, guru kelas 4 dan siswa kelas 4. Objek penelitian budaya sekolah dalam mewujudkan karakter religius. Uji keabsahan data dengan triangulasi sumber dan triangulasi teknik. Analisis data dengan teknik interaktif. Hasil penelitian menunjukkan bahwa: (1) Penerapan budaya sekolah dalam mewujudkan karakter religius, meliputi: pembiasaan melalui kegiatan rutin (dengan membaca Al-Qur’an, menghafalkan password masuk kelas, muroja’ah serta sholat berjamaah (sholat dhuha dan sholat dhuhur)), penguatan karakter anak dalam berakhlak (dengan berdo’a, 5S (senyum, salam, sapa, sopan dan santun) dan adab makan), penguatan karakter anak melalui keteladanan dari guru dalam bertingkah laku dan memberikan motivasi serta evaluasi kegiatan; (2) Kendala penerapan budaya sekolah dalam mewujudkan karakter religius, meliputi: karakteristik siswa yang berbeda-beda, guru belum menjalankan peranan sebagai teladan dan anak kurang mendapat perhatian orang tua. Penelitian diharapkan memberikan informasi baru mengenai budaya sekolah dalam mewujudkan karakter religius di sekolah dasar, sehingga menumbuhkan kepribadian yang baik pada siswa. Kata Kunci: budaya sekolah; karakter; karakter religius